2006
DOI: 10.1086/498969
|View full text |Cite
|
Sign up to set email alerts
|

The Deuterium, Oxygen, and Nitrogen Abundance toward LSE 44

Abstract: We present measurements of the column densities of interstellar D i, O i, N i, and H 2 made with the Far Ultraviolet Spectroscopic Explorer (FUSE ) and of H i made with the International Ultraviolet Explorer (IUE ) toward the sdO star LSE 44 [(l;. This target is among the seven most distant Galactic sight lines for which these abundance ratios have been measured. The H i column density was estimated by fitting the damping wings of interstellar Ly. The column densities of the remaining species were determined w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Concerning isotopic ratios, Penzias (1979) reported that the D/H abundance ratio shows an appreciable gradient with respect to R G from the Galactic center to outside the solar orbit, i.e., 0 kpc R G 12 kpc, with an anomaly in D/H near the Galactic center (Wannier 1980;Lubowich et al 2000). Recent observational studies of D/H in the local ISM reported a uniform single value D/H ∼ 1.5 × 10 −5 within the Local Bubble (Moos et al 2002;Oliveira et al 2003), although variations of factors of 2 or so is also observed in the distant ISM beyond the Local Bubble Wood et al 2004;Hébrard et al 2005;Friedman et al 2006). From a theoretical viewpoint, Prantzos (1996) proposed a chemical evolution model of the Galactic disk with each ring of appropriate width at different Galactocentric distance R G evolving independently under an assumption of homogeneous mixing and instantaneous recycling of the ISM.…”
Section: Lithium Distribution In the Galaxymentioning
confidence: 99%
“…Concerning isotopic ratios, Penzias (1979) reported that the D/H abundance ratio shows an appreciable gradient with respect to R G from the Galactic center to outside the solar orbit, i.e., 0 kpc R G 12 kpc, with an anomaly in D/H near the Galactic center (Wannier 1980;Lubowich et al 2000). Recent observational studies of D/H in the local ISM reported a uniform single value D/H ∼ 1.5 × 10 −5 within the Local Bubble (Moos et al 2002;Oliveira et al 2003), although variations of factors of 2 or so is also observed in the distant ISM beyond the Local Bubble Wood et al 2004;Hébrard et al 2005;Friedman et al 2006). From a theoretical viewpoint, Prantzos (1996) proposed a chemical evolution model of the Galactic disk with each ring of appropriate width at different Galactocentric distance R G evolving independently under an assumption of homogeneous mixing and instantaneous recycling of the ISM.…”
Section: Lithium Distribution In the Galaxymentioning
confidence: 99%
“…The fraction of H 2 along these sight BD +39 3226, and TD1 32709, respectively. Hence, for the three sight lines, Friedman et al 2006).…”
Section: Ly Profile Fittingmentioning
confidence: 99%
“…(D/H) LB is not representative of the cosmic material at the present epoch. Indeed, in addition to the early Copernicus results reported above, FUSE has provided extra clues for a significant dispersion in (D/H) ISM beyond the Local Bubble (Friedman et al 2002;Hoopes 62 G. Hébrard et al 2003;Wood et al 2004;Williger et al 2005;Hébrard et al 2005;Friedman et al 2006;Oliveira & Hébrard 2006;Dupuis et al 2009 If a (D/H) ISM canonical value exists, the best way to determine it might be to measure deuterium along the long lines of sight with high column densities. More material is probed, and thus localized anomalies are likely to be averaged out.…”
Section: Deuterium In the Distant Interstellar Mediummentioning
confidence: 97%
“…The probable cause is the N (OI) measurements, performed with the λ1302Å saturated transition in the HST spectra, whereas N (OI) is measured from unsaturated lines in the FUSE bandpass. Hébrard et al (2005) and Friedman et al (2006) have shown examples of systematic effects on column densities due to saturated lines.…”
Section: Deuterium Within the Local Bubblementioning
confidence: 99%
See 1 more Smart Citation